Halal food authenticity: does it matter to you? - Mustafa, Shuhaimi (Universiti Putra Malaysia Press, 2017)
To the Muslims, the claim for Halal is not debatable. The current Halal food industry as required by 1.8 billion Muslims is estimated to be worth USD 1.6 trillion by 2018. In this respect, the Halal food industry is projected to be the fastest growing and most lucrative business segment in the very near future in view of the rapid increase in the Muslim population in the world. This enormous business potential will be further augmented by the preference, on the part of non-Muslims for the “safe, wholesome and clean” food concept referred to as the Halalan toyyiban. The Manufacture of Halal products, especially food requires an uncompromised understanding and knowledge of the Islamic laws and regulations along with the advancement in food processing and complex ingredients in the entire supply chain. However, unethical practices and fraud of the Halal logo is becoming a regular occurrence and poses a threat to the authenticity of halal products. Thus, authentication using specific, sensitive, easy-to-use and reliable scientific techniques based on DNA, proteins, lipids and metabolomics should be performed to complement the conventional audit-based certification process.